PERAN ORANG TUA DALAM PERTUMBUHAN SPIRITUALITAS ANAK: SEBUAH STUDI EKSEGETIS EFESUS 6:1-4 - Waharman Waharman (Manna Rafflesia, 2018)
The role of parents for their children in spiritual growth is very important, and starting from an early age, teaching for children's spiritual growth is not only given to the church, or during Sunday school services but the most important and most important is the role of parents in the family for her children. If noted, there are still many parents who do not realize the importance of their role as parents to educate the spiritual growth of their children. Therefore through this paper, we try to remind the important role of parents in the growth of children.